Experimental investigation of effect of tool path strategies and cutting parameters using acoustic signal in complex surface machining - Bagci, Eyup (JVE INT LTD, 2017)
High productive milling of complex sculptured surfaces is extremely important in many different industries. Determination of the appropriate tool path styles and milling parameters is crucial in ensuring precise surface machining, meeting the better surface integrities and lower tool deflection and forces using process monitoring methods. In this study, sound pressure as a monitoring method is presented for analyzing different tool path strategies and cutting parameters to assess their influence on surface errors, tool deflection, cutting forces, sound pressure level and instantaneous material removal rate on rough machining of complex surfaces with ball end mill. Design and analysis of experiments are performed using factorial design technique and variance analysis. Additionally, the significant parameters affecting the experimental results are introduced. B-rep based method with integrated CAM software is developed to calculate the cutter/workpiece engagement, effective cutting diameter and instantaneous material removal rate. Milling strategies employed include contour parallel, zigzag with two cut angle, and spiral. The milling conditions were feed rate and radial depth of cut. The conclusion is that 0 degrees zigzag strategy provokes the lowest cutting forces, tool deflection, surface errors and sound pressure and spiral strategy signifies the worst surface errors and the highest cutting forces. With the increase of feed rate, instantaneous material removal rate increases parallel to rising of machining sound signal, milling forces, tool deflection and machining errors. It is observed that the step over value has less influence on the results. The sound pressure level which has a drastic reference to the material removal rate and removed volume values are detected and experimental results could be figured out with sound pressure.
Keywords: sound pressure; machining; freeform surface; tool deflection; cutting forces; surface errors; SOUND; WEAR; RECOGNITION; GENERATION; SYSTEMS; ERROR; Engineering